Study of the dependence of effective compliances of a plane with an array of circular holes on array parameters - Mokryakov, Vyacheslav Victorovich (Computational Continuum Mechanics, 2010)
Nano-pore structure materials (photonic crystals, porous silicon, zeolites, etc.) are used in different technological processes. Therefore, investigation of the mechanical properties of these materials is of considerable practical interest. These mechanical properties are represented by the relationship between average stresses and effective strains, which can be obtained from the solution of the problem for elastic plane. In this paper, we employ the model of an elastic plane having a biaxial periodic system of holes to analyze the dependence of the effective elastic parameters on the direction of applied loads and the geometrical characteristics of the system. Parameter anisotropy is demonstrated. The abnormally high values of Poisson’s ratio, which are impossible in isotropic media but observed in some anisotropic media, are found.